SOME ASPECTS OF OPTIMIZING THE ACTIVITIES OF EXECUTIVE AUTHORITIES EXERCISING STATE CONTROL OVER THE USE OF WATER RESOURCES - Akhrorov Adkhamjon Asrorkul ugli (Scholars Digest Publishing, 2023)
This article analyzes the use of water resources in the Republic of Uzbekistan, the problems that have arisen, in particular, the daily increase in the level of desertification on the territory of the Republic, as well as the system of competent authorities exercising state control over the sphere, which are considered one of the main factors, their powers. Proposals were also developed to optimize the system of executive authorities exercising state control over the use of water resources in order to eliminate such problems as rational use of water resources, drought and water scarcity faced by the future generation, as well as to organize a single state management body that implements these activities in the region and provide it with all powers. These proposals are justified by the experience of foreign countries.
Keywords: water resources, state control, competent authority, desertification, rational use of water, natural environment, hydrogeological conclusion, permit, underground and surface waters.